Predictors of Prenatal Depression: A Cross-Sectional Study in Rural Pakistan - Khan, Rukhsana; Waqas, Ahmed; Mustehsan, Zille Huma; Khan, Amna Saeed; Sikander, Siham; Ahmad, Ikhlaq; Jamil, Anam; Sharif, Maria; Bilal, Samina; Zulfiqar, Shafaq; Bibi, Amina; Rahman, Atif (Frontiers in Psychiatry, 2021)
Objective: To determine the prevalence and association of prenatal depression with socioeconomic, demographic and personal factors among pregnant women living in Kallar Syedan, Rawalpindi, Pakistan. Methods: Five hundred women in the second and third trimester of pregnancy, living in Kallar Syedan, a rural area of district Rawalpindi Pakistan, were included in the study. Depression was assessed using “Patient health questionnaire” (PHQ9) in Urdu, with a cut-off score of 10. Multi-dimensional scale of perceived social support (MSPSS) was used to assess perceived social support. Life Events and Difficulties Schedule (LEDS) were used to measure stressful life events in past one year. Tool to assess intimate partner violence (IPV) was based on WHO Multi Country Study on “Women’s Health and Domestic Violence against Women”. Results: Prevalence of prenatal depression was found to be 27%. Number of pregnancies was significantly associated with prenatal depression (p<0.01). Women living in a joint family and those who perceived themselves as moderately satisfied or not satisfied with their life in the next four years were found to be depressed (p<0.01, OR 6.9, CI 1.77-26.73). Depressive symptomatology in women who experienced more than five stressful life events in last one year was three times higher (p<0.001, OR 3.2, CI 1.68-5.98) than in women with 1-2 stressful events. Women who were supported by their significant others or their family members had 0.9 times (p<0.01, OR 0.9, CI 0.85-0.96) less chance of getting depressed. Pregnant women who were psychologically abused by their partners were 1.5 times more depressed (p<0.05 CI 1.12- 2.51). Odds of having depression was also high in women who had less mean score of MSSI (p<0.05, OR 1.1, CI 1.01-1.09). Women who had suitable accommodation had 0.5 times less chance of having depression than others (p<0.05, OR 0.5, CI 0.27-0.92). Conclusion: Over a quarter of the women in the study population reported prenatal depression, which were predicted predominantly by psychosocial variables.